Whiteness and the Black Fan Imagination: Making Meaning of Whiteness within the Geographies of NASCAR - Vadeboncoeur, Joshua D. (Qualitative Sociology Review, 2022)
This article places its attention on how the spatial boundaries, practices, and separations—as structured by whiteness—impact the contestation and negotiation of meaning-making processes in the production and consumption of NASCAR space(s) for Black fans. It was through that vantage point that the participants demonstrated a nuanced understanding of whiteness, particularly through an awareness of NASCAR as a White space, how to effectively navigate such a White space, and a contextualization of more recent enactments of whiteness within these spaces. To explore and define Black individuals’ racialized experiences and movements as NASCAR fans from their perspective, this article uses a qualitative approach as grounded in narrative inquiry. Thus, findings demonstrate how Black fans make meaning of whiteness within the geographies of NASCAR, which advances theoretical understandings of how whiteness is perceived and represented in the Black imagination. Informed by Southern regional identity and the navigation of White space, these representations of whiteness as exclusive, fearful, and possessive are made salient through NASCAR’s attachment to racialized cultural values.